Femoral artery entrapment after cerclage wiring of distal femoral shaft fracture: A case report - Ukris Gunadham; Thumrong Kongkreangkrai (Journal of Orthopaedics, Trauma and Rehabilitation, 2019)
Femoral artery injury after femoral fracture fixation is a rare complication. Previous literature studies focused mostly on proximal femur fracture. We described a case of superficial femoral artery entrapment after internal fixation augmented with cerclage wire. An 80-year-old female underwent fixation with distal femur locking compression plate augmented with cerclage wire. Six hours after the operation, she developed pulseless limb and computed tomography angiogram showed femoral artery entrapped by cerclage wire. After vascular exploration and cerclage wire removal, the femoral artery returned to normal flow without further complication. We review available literature studies on vascular injury after cerclage wiring especially in the distal part of the femur, the so-called safe zone, for the great care needed before cerclage wiring and the importance of immediate diagnosis and treatment.